CORRECTION OF CARBOHYDRATE METABOLISM BY USING THE APPARATUS OF INSULIN THERAPY IN PATIENTS WITH DIABETES MELLITUS AFTER RENAL TRANSPLANTATION - V. K. Novikov; M. A. Vetlugina; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов)
The article describes using the apparatus of insulin therapy to correct carbohydrate metabolism in patient with diabetes mellitus in postoperative period after renal transplantation. We have noted improvement in indicators of glycemia and reduction the need for exogenous insulin in patients after using the device of insulin therapy.